Noise Reduction Using Gaussian, Mean, And Median Filter To Improve Ultrasonography Image Quality - Mhd. Furqan nasution; Sriani; Ilham Fuadi Nasution (INFOKUM, 2021)
Ultrasound images are captured using high-frequency sound waves to create images with dark and bright spots throughout the subject. In this case, the resulting image will look blurry and some blobs will cause less information on the image. Degraded image quality due to noise. Noise can be caused by physical interference in the acquisition tool or by deliberate mishandling. Due to these problems, there is a need for a system that can enhance ultrasound images by minimizing existing noise. However, many methods have been developed to perform image enhancement by removing noise, which makes one method confusing with which method to use. Therefore, in this study, different methods for removing noise in ultrasound images, such as Gaussian filtering, mean and median, were compared to determine which method is better. The comparison of the three methods is based on PSNR and MSE values. Applied research results show that the median filtering method outperforms Gaussian and Mean methods in reducing noise in USG images to 60%.